PEMBERIAN CIRI LOKAL PADA ARSITEKTUR KOLONIAL LEWAT ORNAMEN PADA AWAL ABAD KE-20 - Handinoto .; SANTOSO, Irwan (Dimensi: Journal of Architecture and Built Environment, 2012)
The purpose of this initial study is to show the existence of efforts in giving local characters to colonial architecture buildings which were built at the end of 19th century and early 20th century. One way is through the use of ornaments or decorative theme themes applied to the building which is using local characters. Some of the ornaments turned out out to be designed by famous artists of that era. The existence of these ornaments slowly disappeared because of the doctrine of modern architecture such as ornament and crime or form follow funtion, etc. which seems to forbid the existence of decorative ornaments on the building. This initial study also identifies people behind the beautiful ornament designs whom are now less well known. They are WOJ Nieuwenkamp (1874-1950) and Jan Toorop (1856-1928) as well as a stained glass maker Jan Schouten (1852-1937), as a leading world-class artists of this era. These people participated in building the colonial buildings in Indonesia early 20th century.